Analysis of Colours of Effutu Festival Costumes for Application in Contemporary Textile Design - Safo-Ankama, Kweku; Sawyerr, Naa Omai (Abdul Media Literasi, 2024)
The Aboakyir festival costumes present a colourful ambience and a panoply of varied colour schemes. The different colour ways and schemes presented by the parade of costumes are always a source of colour inspiration and creative visual sensibilities. The paper attempts to analyze the colours of Effutu festival costumes and their application in contemporary textile design. The study presents inspirational colour palettes on the basis of inspiration from the varied colour schemes presented and applied to contemporary textile designs. Ten (10) colour palettes are generated from different locations, scenes, and activities of the Effutu Aboakyir festival. With the help of the CorelDRAW software, each selected scenery generates a unique colour palette worth applying in contemporary textile designing activities. Each colour palette is applied to textile designs and checked for suitability. Findings revealed that the unique sceneries produce unadulterated colour palettes that could not be easily achieved by other sources of colour inspiration. It was also noted the colours presented on the colour palettes created successful harmonious colour combinations when applied to suitable contemporary textile designs fit for varied applications.